The Evolution of Iranian Carpet Designs with the Influence of Islam and Chinese art; Ilkhanid, Timurid, Safavid - Abouali, ladan; Ni, Jianlin; Kaner, Jake (Journal of History Culture and Art Research, 2020)
This article reviews and analyses the characteristics of Persian rugs through a historical background in the Islamic era, and design motifs that applied to the Persian rugs during the beginning of the Islamic era in Iran. Ilkhanid, Timurid, and Safavid as Islamic dynasties are considered, which were influenced by Chinese design motifs and religious style during said periods. Exemplar rug designs have been selected from illustrations from Shahnameh books (Demotte, Ferdowsi, Shah Tahmasp). Islam and Chinese artists and philosophers had a significant influence on the Persian rug. With the presence of Mongols and Islam in Iran and the establishment of the Ilkhanid dynasty, Chinese design elements had a noticeable effect on the Persian rug. The Mongols with no significant cultural and artistic backgrounds borrowed Chinese design style with Islamic taste applied a new form to their artifacts and goods, which is also highly evident in Iranian carpet design that continued for centuries.